Promoting Application of the International Classification of Functioning， Disability and Health Rehabilitation Set in Musculoskeletal Rehabilitation - YAN Tiebin; XIE Hongwu (康复学报)
The Chinese version of the International Classification of Functioning, Disability and Health Rehabilitation Set (ICF-RS) was first published in China in 2017, and the clinical application of ICF-RS in rehabilitation field in China has gradually increased. This study explores the feasibility and value of ICF-RS in the field of musculoskeletal rehabilitation in China and provides evidence for promoting the clinical application of ICF-RS in an all-round way. This study mainly introduces the development of the International Classification of Diseases (ICD) and International Classification of Functioning, Disability and Health (ICF), the current application of ICF-RS in musculoskeletal rehabilitation and the measures to promote the application of ICF-RS in musculoskeletal rehabilitation. The current application of ICF-RS in musculoskeletal rehabilitation includes the insufficient attention to the functional classification of musculoskeletal rehabilitation, the feasibility analysis and challenges of ICF-RS application in musculoskeletal rehabilitation. It is necessary to raise the awareness of assessing patients' function after orthopaedic surgery timely, clarify the functional orientation of orthopaedic rehabilitation after surgery, accept formal ICF-RS training and improve the convenience of ICF-RS application through APP to promote the application of ICF-RS in the field of musculoskeletal rehabilitation.